PEMBERIAN MAKANAN TAMBAHAN UNTUK MENINGKATKAN KEMAMPUAN MENGIKUTI PELAJARAN PADA SISWA SEKOLAH DASAR - M Husni Tamrin (Jurnal Kependidikan, 2007)
Abstract The aim of the research is to increase the capability of the lesson by giving additional food. The research has been done at the Terbantam I Sleman elementary School within two cycles. The steps of the action that we have done are: (1) To consult and discuss with the principal and teacher class about the plan that conducted the action research, (2) To communicate class teacher for asking how many students who involve and suggest to do some observation about the situation in the class, (3) To give parents some questionnaires about the daily activities  of students like eating, sleeping, playing, and studying,  (4) Direct correction the students achievement of the lesson, (5) To give additional food (6) To correct the teaching methods of the teachers. Result of research: (1) According to the fifth class of the elementary school at Terbantaman I Sleman did not have the side effect of psysic,eg: diarrhea or vomit. Conversely. This program raising the motivation of student in following the lesson, (2) The student present 99.69% follow the lesson, that mean the category was exellent, (3) The task of home work given by teacher 99.9% was done, (4) And the average of the value of the summative of all the lesson are increase. Keywords: food supplement affectivity, elementary school